Evaluation of rail technology a practical human factors guide - Bearman, Chris (Human factors in road and rail transport, 2013)
"Currently, the rail industry lacks a standardized approach to the human factors evaluation of new technologies in operational settings. While a number of human factors evaluation methods exist (such as task analysis, situation awareness measures, quasi-experiments), these are rarely tailored to the industry's needs. This book fills that gap by developing a toolkit of methods that can be used by people in the rail industry to evaluate the human factors implications of new technologies"--Provided by publisher.